Temos todo tempo do mundo?: um estudo sobre percepções temporais e prazer e sofrimento com jovens trabalhadores - Jane Kelly Dantas Barbosa (2018)
Organizations are in a scenario marked by many and constant transformations that results in complex working relationships, intense competition, increasing the use of information and communication technologies, dynamism, speed and time compression. In addition there is the nowadays ways of living, where time is increasingly a shortage good, hard to understand and manage; This way the pressures and demands of everyday life can represent sources of pleasure and suffering for people. The way that people deal with their time, their personal and professional demands, as well as the perception that they have about experiences of pleasure and suffering, may bring reflexes of paramount importance to the organizational context and also to the life of people in many ways. Young workers, an audience marked by idiosyncrasies regarding the group itself and the work context that they are usually inserted, develop preferences and strategies to deal with time and with the sources of pleasure and suffering in their activities, which preferences may impact the performance of young people and the performance of the organization where they develop their first work experiences. Given this, the objective of this work is to analyze how the temporal perceptions and the experiences of pleasure and suffering in the work of young workers assisted by the Professional Social Teaching Association (ESPRO) are related. From this objective, this thesis foments that reflections on the insertion and living of these young people in the corporate world and the possible consequences in their ways of meaning and experiencing the time and the sources of pleasure and suffering, especially in the scope of their productive activities. In order to illustrate this reality, the methodological procedures used are a descriptive, field research, developed through a case study with quantitative and qualitative approaches, characterizing a methodological triangulation. Data collection was made through questionnaires and semi-structured interviews with young workers assisted by ESPRO, from Belo Horizontes branch. Data from the questionnaires were treated using uni and bivariate descriptive statistical analysis, while the interviews were analyzed by content analysis. The results showed that the temporal dimensions and the indicators of pleasure and suffering have significant relations statistically between them, which was corroborated by the interviewees' reports.